Post-harbour areas - new urban space = Tereny poportowe - nowa przestrzeń miejska - Nowacka-Rejzner, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article on selected examples one illustrated the different solutions for shaping post-harbour areas. One highlighted the complexity and longevity of activities conducted in these areas, which include both: the modernization of building structures, shaping of new functional and spatial interactions, reproduction of natural resources, protection and sharing of preserved buildings and complexes of cultural heritage, but also well balanced management of transformed area. The basis for conducted deliberations constitute studies and field studies concerning the development of urban structures, conducted for many years by the author.
Keywords: tereny poportowe; przestrzeń miejska; rewitalizacja; post-harbour areas; urban space; revitalisation